PENGARUH TAYANGAN TELEVISI TERHADAP PERKEMBANGAN AKHLAK SISWA MADRASAH TSANAWIYAH RAUDHATUL HUDA KECAMATAN NEGERI KATON - Neneng Diani (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
This study aims to determine the influence of television shows such as soap operas, animated cartoons, and music entertainment on the development of students’ akhlaq (moral behavior) in grade VIII of Raudhatul Huda Kecamatan Negeri Katon, South Lampung Regency. Additionally, this study aims to determine the extent of the negative impact of television shows on students’ akhlaq behavior. This research uses a quantitative approach with a population of 90 students from grade VIII classes consisting of VIII A and VIII B, because the population is less than 100 and can be researched comprehensively. The data collection methods used in this study are observation, questionnaire, and documentation. The data analysis techniques used in this study are descriptive statistical analysis using percentages and frequencies to determine the characteristics of each respondent, and inferential statistical analysis using correlation analysis, simple linear regression analysis, and hypothesis testing. The results of this study show that based on the partial analysis (t-test), television shows (X) have an influence on the development of students’ akhlaq behavior (Y) with a t-value of 4.264. This can be seen from the fact that the t-value> t-table (4.264> 1.987), indicating that Ho is rejected and Ha is accepted, meaning that television shows (X) have an influence on the development of students’ akhlaq behavior (Y) and the value of 0.171 on the akhlaq development variable can be explained by television shows, while the remaining 82.9% of students’ akhlaq development is influenced by unexamined variables. Therefore, television shows significantly influence the negative development of students’ akhlaq behavior in grade VIII of Raudhatul Huda Kecamatan Negeri Katon, South Lampung Regency. This can be explained by evidence that shows that television shows can cause behavior that is not in line with students’ moral behavior in general.